A Girl with Delayed Puberty and Bumpy Lips. - Andrade, Stefanny; Sirchia, Fabio; Faleschini, Elena; Barbi, Egidio (J Pediatr, 2018)
Keywords: Adolescent; Exons; Female; Genes, Dominant; Humans; Lip; Multiple Endocrine Neoplasia Type 2b; Neoplasm Metastasis; Puberty, Delayed; Thyroid Neoplasms; Thyroidectomy; Tongue

A Klinefelter boy with congenital adrenal hyperplasia: too much or too little androgens? - Zanella, Giada; Tornese, Gianluca; Mascheroni, Elisabetta; Faleschini, Elena; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: The simultaneous occurrence of Klinefelter Syndrome (KS) and Congenital Adrenal Hyperplasia (CAH) is an exceptional event: there are just three case reports (two children and a 51 years old man) describing males affected by both KS and 21OHD (21-hydroxylase deficiency) CAH, the first causing androgen deficiency, the latter leading to androgen excess. CASE REPORT: We report the 4th case of association of KS and CAH in a young man with CAH with good androgen control and with normal secondary sex characteristics, whose Klinefelter syndrome was diagnosed because of reduced testicular volume. He was the first reported case of association of KS and CAH who started androgen replacement therapy in the pubertal age and whose pubertal development was described and followed up step by step. CONCLUSION: In a boy with CAH and small testicular volume, it's important to consider that hypogonadism may be masked by the adrenal androgens excess and a karyotype should be performed once testicular adrenal rests have been ruled out.
Keywords: Adolescent; Adrenal Hyperplasia, Congenital; Androgens; Follow-Up Studies; Hormone Replacement Therapy; Humans; Klinefelter Syndrome; Male; Rare Diseases; Risk Assessment; Testis

An unusual unilateral breast enlargement in a prepubertal girl. - Pavan, Matteo; Faleschini, Elena; Tornese, Gianluca; Zandonà, Lorenzo; Ventura, Alessandro (Arch Dis Child, 2018)

The incidence rate and prevalence of pediatric type 1 diabetes mellitus (age 0-18) in the Italian region Friuli Venezia Giulia: population-based estimates through the analysis of health administrative databases. - Valent, Francesca; Candido, Riccardo; Faleschini, Elena; Tonutti, Laura; Tortul, Carla; Zanatta, Manuela; Zanette, Giorgio; Zanier, Loris (Acta Diabetol, 2016)
AIMS: The main objective of this study was to estimate the incidence rate and prevalence of pediatric type 1 diabetes mellitus (T1DM; population 0-18 years of age) in the northeastern Italian region Friuli Venezia Giulia and to characterize the subjects affected by the disease. METHODS: This was a retrospective population-based study conducted through the individual-level linkage of several health administrative databases of the Friuli Venezia Giulia region. The incidence rate and prevalence were calculated in the population 0-18 years of age. Using the Mid-p exact method, 95 % confidence intervals for rates were calculated. RESULTS: The incidence rate of pediatric T1DM in the years 2010-2013 was 15.8 new cases/100,000 person-years, peaking in the age class 10-14 years. The rate has increased substantially as compared with the previous regional estimate that dated back to 1993. We observed a seasonal pattern both in the date of birth of the incident cases and in the date of onset of the disease. In the region in 2013, there were 294 prevalent cases (15.1/10,000 inhabitants). Most of them had at least one glycated hemoglobin test in the year. More than 15 % had co-existing autoimmune comorbidities. CONCLUSIONS: The incidence rate of pediatric T1DM in Friuli Venezia Giulia has increased in the last years, and the disease is a relevant public health issue in the region.

A case of Rubinstein-Taybi syndrome associated with growth hormone deficiency in childhood. - Tornese, Gianluca; Marzuillo, Pierluigi; Pellegrin, Maria Chiara; Germani, Claudio; Faleschini, Elena; Zennaro, Floriana; Grandone, Anna; Miraglia Del Giudice, Emanuele; Perrone, Laura; Ventura, Alessandro (Clin Endocrinol (Oxf), 2015)

Relapse and metastasis of atypical teratoid/rhabdoid tumor in a boy with neurofibromatosis type 1 treated with recombinant human growth hormone. - Tornese, Gianluca; Faleschini, Elena; Matarazzo, Lorenza; Bibalo, Cristina; Zanazzo, Giulio Andrea; Rabusin, Marco; Tonini, Giorgio; Zennaro, Floriana; Ventura, Alessandro (Neuropediatrics, 2015)
Even though no increased recurrence rate seems to be reported in patients with brain tumors receiving recombinant human growth hormone (rhGH) replacement, in some patients multiple risk factors could put at higher risk for recurrence. In such cases, the decision to start rhGH therapy should be very cautious. A boy with neurofibromatosis type 1 developed an atypical teratoid/rhabdoid tumor (AT/RT) of right cerebellum, treated with surgery, radiotherapy, and chemotherapy. After 3 years of remission, he started rhGH for growth hormone deficiency, having a negative magnetic resonance imaging (MRI) scan. Ten weeks after starting therapy, the boy became symptomatic and MRI showed relapse of AT/RT in the right cerebellum and a new lesion in the brainstem. The boy died of progressive disease. In this case, the connection between AT/RT recurrence and the beginning of rhGH therapy, with a negative pretreatment MRI, cannot be excluded. Additional caution should be used for rhGH in patients with multiple risk factors.
Keywords: Brain Stem Neoplasms; Cerebellar Neoplasms; Child; Human Growth Hormone; Humans; Magnetic Resonance Imaging; Male; Neurofibromatosis 1; Recombinant Proteins; Recurrence; Rhabdoid Tumor; Risk Factors; Teratoma

Sirolimus Therapy in Congenital Hyperinsulinism: A Successful Experience Beyond Infancy. - Minute, Marta; Patti, Giuseppa; Tornese, Gianluca; Faleschini, Elena; Zuiani, Chiara; Ventura, Alessandro (Pediatrics, 2015)
Congenital hyperinsulinism (CHI) due to diffuse involvement of the pancreas is a challenging and severe illness in children. Its treatment is based on chronic therapy with diazoxide and/or octreotide, followed by partial pancreatectomy, which is often not resolutive. Sirolimus, a mammalian target of rapamycin inhibitor, was reported to be effective in treating CHI in infants. We report here the case of an 8-year-old boy affected by a severe form of CHI due to a biallelic heterozygous ABCC8 mutation who responded to sirolimus with a dramatic improvement in his glucose blood level regulation and quality of life, with no serious adverse events after 6 months of follow-up. To the best of our knowledge, this is the first report of a successful intervention in an older child. It provides a promising basis for further studies comparing sirolimus with other treatments, particularly in older children.

Type 1 diabetes mellitus and celiac disease: usefulness of gluten-free diet. - Pascolo, Paola; Faleschini, Elena; Tonini, Giorgio; Ventura, Alessandro (Acta Diabetol, 2013)

Hepatic glycogenosis in an adolescent with diabetes. - Bua, Jenny; Marchetti, Federico; Faleschini, Elena; Ventura, Alessandro; Bussani, Rossana (J Pediatr, 2010)
Keywords: Adolescent; Diabetes Mellitus, Type 1; Female; Glycogen Storage Disease; Humans; Liver Diseases